2020
DOI: 10.7498/aps.69.20200588
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of atmospheric water vapor vertical column concentration and vertical distribution in Qingdao using multi-axis differential optical absorption spectroscopy

Abstract: The method of retrieving the vertical column density (VCD) and the atmospheric vertical profile of water vapor in visible blue band (434.0–451.5 nm) were studied by using the multi-axis differential optical absorption spectroscopy (MAX-DOAS). First, the method of retrieving the VCD of water vapor was studied. Owing the the fact that the water vapor absorption cross section is of high resolution and it cannot be effectively measured by MAX-DOAS, a convolved cross section with the instrument slit function was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Because H 2 O saturation absorption was neglected for this retrieval band (Lampel et al., 2015), it may have had some effect on the MAX‐DOAS data, when H 2 O concentration was higher. Studies have shown that when the H 2 O DSCD reaches 4 × 10 23 molec./cm 2 , the saturation absorption effect will reduce the OD by 1.76% (Ren et al., 2020), and when the H 2 O DSCD reaches 1 × 10 24 molec./cm 2 , the saturation absorption effect will reduce the OD by 4.23%. In this study, the maximum H 2 O DSCD was 9.85 × 10 23 molec./cm 2 , and the data between 4 × 10 23 and 9.85 × 10 23 molec./cm 2 in June, July, August, and September accounted for 23.38%, 44.02%, 64.66%, and 33.39% of the total data, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Because H 2 O saturation absorption was neglected for this retrieval band (Lampel et al., 2015), it may have had some effect on the MAX‐DOAS data, when H 2 O concentration was higher. Studies have shown that when the H 2 O DSCD reaches 4 × 10 23 molec./cm 2 , the saturation absorption effect will reduce the OD by 1.76% (Ren et al., 2020), and when the H 2 O DSCD reaches 1 × 10 24 molec./cm 2 , the saturation absorption effect will reduce the OD by 4.23%. In this study, the maximum H 2 O DSCD was 9.85 × 10 23 molec./cm 2 , and the data between 4 × 10 23 and 9.85 × 10 23 molec./cm 2 in June, July, August, and September accounted for 23.38%, 44.02%, 64.66%, and 33.39% of the total data, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It can be set to 1 and then modified according to the iteration. The generality of the PriAM algorithm for aerosols, NO 2 , SO 2 , HCHO, and H 2 O has been proven in many comparative observation experiments [29,31,32,34,35,[50][51][52].…”
Section: Profile Retrievalmentioning
confidence: 99%
“…Multi-axis differential optical absorption spectroscopy (MAX-DOAS) is a passive DOAS remote sensing technology developed in recent years [26], featuring a low cost, simple instrument setup, mature algorithm, and high spatiotemporal resolution. MAX-DOAS can measure the vertical distribution of a variety of trace gases (NO 2 , SO 2 , HCHO, HONO, and CHOCHO), aerosols, and water vapor in the atmosphere [14,[27][28][29][30][31][32][33], thus providing a basis for the study of haze and dust pollution. In addition, the gas transport fluxes can be measured by coupling the gas profile retrieved from MAX-DOAS measurements with the wind profile [31,34], which is significant for the study of gas transport.…”
Section: Introductionmentioning
confidence: 99%
“…Although LIDAR detection accuracy is high, the detection range is limited. The sounding balloon can simultaneously detect a variety of atmospheric parameters and detection heights up to 30 km, but the cost is high, and the path is not controllable [7]. A ground-based Fourier transform spectrometer with high resolution is capable of trace gas measurement in atmospheric columns, but the device is usually large and expensive.…”
Section: Introductionmentioning
confidence: 99%